PELAKSANAAN PENERIMAAN PAJAK BUMI DAN BANGUNAN OLEH DINAS PENDAPATAN DAERAH KABUPATEN BENGKALIS TAHUN 2017 (Studi di UPT Kecamatan Mandau) - Fina Novianti; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Land and Building Tax included the state tax collected by the Bengkalis Regency Government is reliable enough to increase local revenues in Bengkalis Regency so that it can improve people's lives. The formulation of the problem in this study is why the Implementation of Land and Building Tax Receipts by the Bengkalis Regency Regional Revenue Service in 2017 (Study at UPT Sub-District of Mandau) has not been maximized.The purpose of this study is to describe the Implementation of the Receipt of Land and Building Tax Collection by the Bengkalis Regency Regional Revenue Service in 2017 (Study at UPT Mandau District). This research is a qualitative study conducted at the Regional Revenue Unit of Mandau District. The techniques used to collect data in this study are (1) Interviews and (2) Documentation.The conclusion of this study shows that the implementation of Land and Building Tax Revenue at the Regional Income of the District of Mandau is included in the category of less than the maximum. The constraints in the implementation of Land and Building Tax Receipts by the Bengkalis Regency Regional Revenue Service in 2017 are the lack of public response to the awareness of paying taxes, re-registration that has not been completed by officials against taxpayers who have problems with their SPPT, and do not understand some people with the procedures pay taxes.  Keywords: revenue, land and building tax